2007
DOI: 10.1038/sj.jid.5700713
|View full text |Cite
|
Sign up to set email alerts
|

IL-20 Gene Expression Is Induced by IL-1β through Mitogen-Activated Protein Kinase and NF-κB-Dependent Mechanisms

Abstract: IL-20 is a novel member of the IL-10 cytokine family with pleiotropic effects. Current knowledge of what triggers and regulates IL-20 gene expression is sparse. The aim of this study was to investigate the regulation of IL-20 expression in cultured normal human keratinocytes. The expression of IL-20 was rapidly induced by proinflammatory stimuli, in particular IL-1beta, IL-6, and UVB irradiation. Using kinase inhibitors and small-interfering RNA, we discovered that the p38 mitogen-activated protein kinase (MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 40 publications
5
69
0
Order By: Relevance
“…These results extend observations on stimulation of IL-20 upon hypoxia (Chen and Chang, 2009) and UVB irradiation (Hunt, et al, 2006). Both IL-20 and IL-24 expression is dependent on p38 MAPK (Otkjaer, et al 2010;Otkjaer, et al, 2007), which is increased in KS cells (own unpublished results). This cytokine has been shown to specifically inhibit the activation of NF-kappaB induced by interleukin 1 family, member 6 (Blumberg, et al, 2007), but its contribution to KS phenotypes remains to be established.…”
Section: Inflammation and Dermal Fibrosis In Ks Skin In Vivosupporting
confidence: 77%
See 1 more Smart Citation
“…These results extend observations on stimulation of IL-20 upon hypoxia (Chen and Chang, 2009) and UVB irradiation (Hunt, et al, 2006). Both IL-20 and IL-24 expression is dependent on p38 MAPK (Otkjaer, et al 2010;Otkjaer, et al, 2007), which is increased in KS cells (own unpublished results). This cytokine has been shown to specifically inhibit the activation of NF-kappaB induced by interleukin 1 family, member 6 (Blumberg, et al, 2007), but its contribution to KS phenotypes remains to be established.…”
Section: Inflammation and Dermal Fibrosis In Ks Skin In Vivosupporting
confidence: 77%
“…Thus far, little has been known about the functions of these cytokines in the skin. A recent study reported their induction after skin injury (Roupe, et al, 2010), and previous investigations suggested regulation of these interleukins through stress induced pathways (Chen and Chang, 2009;Hunt, et al, 2006;Otkjaer, et al, 2010;Otkjaer, et al, 2007). To corroborate this in KS, we used three different well-established methods -hypoxia, oxidative stress and UVB irradiation -to induce cell stress in normal and KS keratinocytes and showed that stress enhances expression and secretion of IL-20 and IL-24 by KS cells.…”
Section: Inflammation and Dermal Fibrosis In Ks Skin In Vivomentioning
confidence: 98%
“…IL-20 is induced when IL-1␤ modulates p38 MAPK and the NF-B-dependent pathway (49). NF-B mediates ischemia-induced neuronal death via IB kinase (50).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown at 37˚C and 5% CO 2 in a humidified incubator. We have previously reported that this protocol routinely results in very pure keratinocyte cultures with .95% keratin 14-positive cells (21). Fresh medium was added every second day.…”
Section: Cellsmentioning
confidence: 99%